At the margins: phonology and phonetics of Zongozotla Totonac glottalization - Garellek, Marc; López-Francisco, Osbel; Amith, Jonathan D. (Laboratory phonology, 2025)
Glottal stops and glottalized (“laryngealized”) vowels in Totonac and Tepehua languages are crucial for historical reconstructions, but their phonological and phonetic properties have often posed analytic problems for synchronic descriptions. In this paper, we provide in-depth phonological and phonetic analyses of glottal stops and glottalized vowels in the variety of Totonac spoken in Zongozotla, Puebla State, Mexico. We argue that glottal stops and glottalized vowels are marginal in this language: glottal stops only appear phrase-finally, and the vocalic phonation contrast has a low functional load in addition to being phonetically weak. And though glottal stops and glottalized vowels are in complementary distribution, we argue that they should be treated as distinctive sounds in the language. We provide possible diachronic explanations for many of the attested patterns, and highlight the implications for diachronic and synchronic studies of Totonacan glottalization. Overall, our paper provides a detailed, unified analysis of glottal stops and glottalized vowels in Totonac, as well as evidence for the role of postlexical structure in creating “intermediate phonological relationships” at the lexical level. [Totonac translation of abstract:] Lu:xlakaskinka n pi tanksi natsuqa:wi kintachiwi:nkani n tu li:laqapaskani n tatanakuh, akxní la:xaqatli:yá:’w, xli:xlitá lantla ma:tsawaji:ya:’wi n kinkilhpi:nkani n chu: n kiaqapixnikani akxní n chiwi:naná:’w, akxní wana:’wi qalhtám tachiwi:ni wa ni:má n pala ka a:wán li:ma:qalhsputananá:’w, chu: wa ni:má ka kilhpu:laktanu:namah. Chaná n chu: na:má nali:aqataqsa:wi la:ntla n talaqpaliti:lhiyi n kintachiwi:kán, n chu: la:ntla n kilhtsukiní:’t.  Wa:mpí lu:qalhí xlaqasi lantla n tatsawaji:yi iyma: n kiaqapixnikani akxní n chiwi:naná:’w, n pi na: chaná n chu: n ta’wa laqtsuqki:kán. Kli:qalhtawaqama:’wi kini la:ntla tlaq tla:ni nalaqtsuqki:ya:’wi n kintachiwi:kani u:má kZongozotla, Puebla, México. Tla:ni kini nakwana:’wi n pi nilakxtami wanqo:’ya:’wi qalhtanu tachiwi:ni akxní n pala ka li:ma:qasputanana:’wi jkintaqalhchiwi:kani n chu wa ni:má n ka xlakyita:’ti n kilhpu:laktanu:namah, n pi na: chaná n chu: lu:ta’wa n qaxmatkán, xpa:lakata n pi ka ni:ni:má lantla n talaqpalí:qo:’y. Tanksi kini klaqxkutni:’ta:’wi n chu: na: tanksi kma:aqataqsni:nana:’wi xkilhtsúkuti n kintachiwi:kani iyma: n tatanaku n chu: la:ntla n talaqpali:tílhalhi wa lantla ma:tsawajiya:’wi n kinkilhpi:nkani n chu: n kiaqapixnikani akxní n chiwi:naná:’w. Kli:qalhtawaqani:’ta’wi kini lantla n tlawaqo:’ya:’wi n qalhtanu tachiwí:n, n chu: kma:siyiya:’wi lantla talaqpali:qo:’yi wa:ntú wampatana:’wi maski lu:ká ni:ni:má wa lantla n talaqpali:qó:’y. [Spanish translation of abstract:] Cómo representar apropiadamente los cierres glotales y las vocales glotalizadas (o “laringizadas”) en la familia totonaco-tepehua es esencial para la reconstrucción del protosistema de esta lengua. Sin embargo, las propiedades fonológicas de la glotalización y su realización fonética representan un desafío en las descripciones sincrónicas.  En este artículo analizamos los patrones fonológicos y fonéticos de los cierres glotales y las vocales glotalizadas en el totonaco de Zongozotla, Puebla, México. Proponemos que estos sonidos son marginalmente fonémicos: los cierres glotales aparecen únicamente a final de frase, y el contraste entre vocales con voz modal y voz glotalizada tiene una carga funcional baja, además que su realización fonética es muy débil. Aunque los cierres glotales y las vocales glotalizadas están en distribución complementaria, argumentamos que deben ser tratados como sonidos contrastivos en esta lengua. Proporcionamos explicaciones diacrónicas para muchos de los patrones atestiguados y destacamos las implicaciones para los estudios diacrónicos y sincrónicos de la glotalización en el totonaco. En general, nuestro artículo proporciona un análisis detallado y unificado de los cierres glotales y las vocales glotalizadas en el totonaco, y a su vez, provee evidencias del papel que juega la estructura postléxica en la creación de “relaciones fonológicas intermedias” a nivel léxico.